Characterization of a New Structured Packing by Computational Fluid Dynamics. Issue 1 (27th November 2020) - Hassanvand, Amin; Esmaeili-Faraj, Seyyed Hamid; Moghaddam, Mojtaba Saei; Moradi, Rasoul
Abstract: The novel wire gauze structured packing PACK‐1300Y with high specific surface area was characterized by computational fluid dynamics. The main features of PACK‐1300Y were investigated including the dry and wet pressure drop as well as the height equivalent to a theoretical plate (HETP). Moreover, the flow structure of this packing was described via numerical simulations. To evaluate the amount of HETP and dry and wet pressure drop, 3D computational fluid dynamic modeling with respect to the Eulerian‐Eulerian multiphase approach was applied. The average relative errors were determined between the findings achieved from computational fluid dynamic simulation and experimental findings for mass transfer efficiency and wet and dry pressure drop, respectively. Abstract : A computational fluid dynamics approach was performed to characterize the wire gauze structured packing PACK‐1300Y and investigate the key hydrodynamic parameters of this packing such as dry/wet pressure drop and the height equivalent to a theoretical plate for the air/water system. The employed numerical approach proved to be applicable to obtain reliable outcomes for these kinds of devices.